Pelatihan Laporan Keuangan dengan Google Spreadsheet dalam Rangka Meningkatkan Pengetahuan UMKM - Puspita Rama Nopiana; Gusnafitri Gusnafitri; Wellia Novita; Yohan Fitriadi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
This activity is motivated by technological developments that demand online activities, so micro, small and medium enterprises (MSMEs) must have a strategy for developing their business, especially starting to improve financial management to see the development and growth of their business in each period. The PKM team conducts training on making financial reports using Google Sheets which provides knowledge and understanding to MSMEs in the city of Padang, so they can manage finances properly. The method used in this training is the lecture method, in which material exposure and training methods are given, where participants are asked to practice preparing their business financial reports, as well as discussion methods, participants and resource persons discuss in solving the problems they face. The results of this activity 1) Participants can find out that their business is included in the small / micro / prevent category from the turnover they get; 2) Participants know that the complete financial statements can help analyze their financial performance, because so far they only record the results of their business with a list of money in and money out books only; 3) Participants gain new knowledge that input using the MS. Excel application can be displayed and controlled online through Google Sheets media, especially if not at the place of business. This activity can make a positive contribution to participants by 80% to their business development.